Effects of Pregnancy and Isoniazid Preventive Therapy on Mycobacterium tuberculosis Interferon Gamma Response Assays in Women With HIV. (28th July 2020) - Weinberg, Adriana; Aaron, Lisa; Montepiedra, Grace; Sterling, Timothy R; Browning, Renee; Mmbaga, Blandina; Vhembo, Tichaona; Naik, Shilpa; Kabugho, Enid; Masheto, Gaerolwe; Pahwa, Savita; Mathad, Jyoti S; et al.
Abstract: Background: Pregnancy is accompanied by immune suppression. We hypothesized that Mycobacterium tuberculosis -specific inflammatory responses used to identify latent tuberculosis infection (LTBI) lose positivity during pregnancy. We also hypothesized that isoniazid preventive therapy (IPT) may revert LTBI diagnoses because of its sterilizing activity. Methods: 944 women with human immunodeficiency virus infection (HIV) participating in a randomized, double-blind, placebo-controlled study comparing 28 weeks of IPT antepartum versus postpartum, were tested by QuantiFERON-gold-in-tube (QGIT) antepartum and by QGIT and tuberculin skin test (TST) at delivery and postpartum. Serial QGIT positivity was assessed by logistic regression using generalized estimating equations. Results: From entry to delivery, 68 (24%) of 284 QGIT-positive women reverted to QGIT-negative or indeterminate. Of these, 42 (62%) recovered QGIT positivity postpartum. The loss of QGIT positivity during pregnancy was explained by decreased interferon gamma (IFNγ) production in response to TB antigen and/or mitogen. At delivery, LTBI was identified by QGIT in 205 women and by TST in 113 women. Corresponding numbers postpartum were 229 and 122 women. QGIT and TST kappa agreement coefficients were 0.4 and 0.5, respectively. Among QGIT-positive women antepartum or at delivery, 34 (12%) reverted to QGIT-negative after IPT. There were no differences between women who initiated IPT antepartum or postpartum. Conclusions: Decreased IFNγ responses in pregnancy reduced QGIT positivity, suggesting that this test cannot reliably rule out LTBI during pregnancy. TST was less affected by pregnancy, but had lower positivity compared to QGIT at all time points. IPT was associated with loss of QGIT positivity, the potential clinical consequences of which need to be investigated. Abstract : Adriana Weinberg, Lisa Aaron, Grace Montepiedra, Timothy R. Sterling, Renee Browning, Blandina Mmbaga, Tichaona Vhembo, Shilpa Naik, Enid Kabugho, Gaerolwe Masheto, Savita Pahwa, Jyoti S. Mathad, Sylvia M. LaCourse, Katie McCarthy, Sarah Bradford, Gerhard Theron, Diane Costello, Bonnie Zimmer, Marie F. Pierre, Kamunkhwala Gausi, Paolo Denti, David W. Haas, and Amita Gupta; for the IMPAACT P1078 study team The sensitivity of QuantiFERON-gold-in-tube decreased during pregnancy. QuantiFERON-gold-in-tube and tuberculin skin testing had modest agreement, with QuantiFERON-gold-in-tube more likely to detect latent TB infection. 12% of participants positive by QuantiFERON-goldin-tube during pregnancy became negative after completion of isoniazid treatment.